Kinerja Program Pendidikan di Kabupaten Kepulauan Yapen Provinsi Papua - Ibrahim Kristofol Kendi (Syntax Literate, 2023)
Papua's Special Autonomy Policy, which is an opportunity to catch up with human resource development, has not been able to provide changes, especially education issues in the Land of Papua, especially in the Yapen Islands District, Papua Province. This research method is descriptive quantitative research. The results of this study showed that the percentage of school enrollment rate for residents of 7-12 years targeted at 99.22% of local governments succeeded in realizing 97.02% and a difference of 2.2%. Although it has not yet reached the target, this number is relatively small, meaning that the local government is quite successful in opening access to education for the community to receive elementary school education. Success in achieving the School Participation Rate target for residents aged 7-12 years and 13-15 years was not followed by the Participation Rate of residents aged 16-18 years. The local government targets 94.65% that has been achieved is 84.27%, a difference of 10.38%. The low participation rate is caused by the lack of educational infrastructure, especially high schools, which are only available in 3 districts out of 14 districts in Yapen Islands Regency. The conclusion in this study is that the high school enrollment rate is largely determined by the availability of existing infrastructure. The local government has prepared adequate educational infrastructure specifically for high schools in all districts or at least adjacent districts.